Waste Management in Kediri District - Indasah; Nurul Puspa Irawati (STRADA : Jurnal Ilmiah Kesehatan, 2025)
This Waste Management Research in Kediri Regency aims to examine the technical operational aspects, policies and regulations, financing, institutions, community participation, and obstacles in waste management in Kediri Regency. This research is descriptive qualitative. From the results of this study, conclusions can be drawn. Technical operational aspects, the percentage of waste handling in Kediri Regency is 12%. Policy and regulatory aspects are considered still low. Financing aspects, the budget is still low. The institutional aspects that are running are only focused on the "Reduce, Reuse, Recycle" Waste Processing Place (TPS3R). The aspect of community participation, namely the large number of people who feel they do not need collective waste management.